Kategoriernes kamp - Debatten om en verdenslitteratur på fransk - Verstraete Hansen, Lisbeth (Passage - Tidsskrift for litteratur og kritik, 2012)
Lisbeth Verstraete Hansen: “The Battle of Categories. The Debate about a World Literature in French” This article questions the literary vision expressed in the manifesto Pour une littérature-monde en français. The article examines the binary oppositions constructed by the signatories in order to position themselves in the literary field (francophone literatures vs literature-monde en français, literary formalism vs real world /mobility), then shows that the attempt to define an aesthetic ideal common to all writers is vain. Finally, an analysis of Alain Mabanckou’s novel Verre Cassé (2005) demonstrates how this writer could be said to have textually realized his personal vision of a literature-monde en français considered as a plurality of experiences. The article concludes that the manifesto’s influence is more visible in academic debate about categorizations in literary history than in literary works.